The Salutogenic Approach to Developing Healthy Eating Behaviors in People with Diabetes Type 2: A Literature Review - Ma'rifati, Aisyah Aulia (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2026)
Background: This literature review examines the rising prevalence of Type 2 Diabetes Mellitus (T2DM), which is largely influenced by unhealthy dietary behaviours and the limited effectiveness of traditional cognitive-based interventions. It explores the Salutogenic Model as an alternative framework that emphasizes individuals’ capacity to use available resources and maintain a strong Sense of Coherence (SoC) to support healthy eating behaviours. Purposes: The aim of this review is to identify and analyze current evidence on how the salutogenic approach supports the development of healthy dietary behaviours and enhances well-being in people with Type 2 Diabetes. Method: This review followed the PRISMA method to systematically search PubMed, Scopus, and Google Scholar (2015–2025) for studies on the salutogenic approach, Sense of Coherence, and healthy eating in individuals with Type 2 Diabetes Mellitus. Study quality was appraised using the CASP Qualitative Checklist for qualitative research and the JBI Critical Appraisal Checklists for quantitative designs, ensuring rigorous and design-appropriate evaluation of methodological validity. Results: The review found consistent evidence that the salutogenic model, particularly through the SALUD program, significantly improves Sense of Coherence, stress regulation, and healthy eating behaviours among individuals with Type 2 Diabetes Mellitus. Empirical findings also show strong peer support effects and sustained behaviour change up to six months post-intervention. Conclusion: The salutogenic model changes T2DM care by focusing on building personal and social resources. It has the potential to improve resilience, promote healthy eating, and encourage long-term self-management. However, its effectiveness relies on sufficient support, trained professionals, and adjustments at cultural and system levels.